2009
DOI: 10.1083/jcb.200901042
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β phosphorylation modulates CLASP–microtubule association and lamella microtubule attachment

Abstract: Polarity of the microtubule (MT) cytoskeleton is essential for many cell functions. Cytoplasmic linker–associated proteins (CLASPs) are MT-associated proteins thought to organize intracellular MTs and display a unique spatiotemporal regulation. In migrating epithelial cells, CLASPs track MT plus ends in the cell body but bind along MTs in the lamella. In this study, we demonstrate that glycogen synthase kinase 3β (GSK3β) directly phosphorylates CLASPs at multiple sites in the domain required for MT plus end tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
226
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(250 citation statements)
references
References 55 publications
23
226
1
Order By: Relevance
“…Depletion of CRMP2 had no effect on MT stabilization or virus spread, demonstrating specificity in the GSK3β-regulated +TIPs that contribute to the biology of infection. CLASPs mediate MT stabilization in response to GSK3β inactivation and MT orientation toward the leading edge of motile cells and neuronal growth cones (29,(41)(42)(43). Similar to HSV-1-infected cells, depletion of CLASPs results in MT looping (43) and reduced levels of Ac-MTs (29,41,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of CRMP2 had no effect on MT stabilization or virus spread, demonstrating specificity in the GSK3β-regulated +TIPs that contribute to the biology of infection. CLASPs mediate MT stabilization in response to GSK3β inactivation and MT orientation toward the leading edge of motile cells and neuronal growth cones (29,(41)(42)(43). Similar to HSV-1-infected cells, depletion of CLASPs results in MT looping (43) and reduced levels of Ac-MTs (29,41,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…To date, these include MAP1b, Tau, ACF7, and CLASP2 (49,50,52,53). It has been suggested that the polarized migration of cells in general requires local GSK3␤ inhibition at the leading edge (52,54,55).…”
Section: Crmp Expression Generates Stable Interphase Microtubules-mentioning
confidence: 99%
“…This finding does not imply that all phosphorylation of CLASP2 is controlled by the MAPK pathway, raising the possibility that CLASP2 may undergo PI3K-controlled phosphorylation in response to insulin as well. In support of this hypothesis, it has been shown that GSK3␤, a kinase known to be deactivated by insulin-stimulated Akt (25,26), phosphorylates CLASP2, leading to disruption of the association of CLASP2 with MTs (13). In this case, insulin would suppress GSK3␤ phosphorylation sites within CLASP2.…”
Section: Discussionmentioning
confidence: 68%
“…Current indirect evidence supports a role for CLASP2 in insulin action. Glycogen synthase kinase 3␤ (GSK3␤), a kinase known to be deactivated by insulin-stimulated Akt, phosphorylates CLASP2, leading to disruption of the association of CLASP2 with MTs (13,14). CLASP2 associates with LL5␤, a pleckstrin homology (PH) domain-containing protein that interacts with PI3K-generated PIP 3 (9,15).…”
mentioning
confidence: 99%